Avaliação de substâncias de interesse biológico com propriedades anti e pró-oxidantes - Silva, Thaissa Lúcio (2014)
Quinones present significant biological activities such as anticancer, anti-inflammatory, antioxidant, antiviral and antifungal. The molecular pathways related to the bioactivity of quinones include: oxidative stress (OS), bioreductive alkylation (BRA) by generating electrophilic intermediates, Michael addition of various nucleophilic endobiotics and also through metal complexation, with similar mechanisms and sometimes enhanced effects. The detrimental effect of ROS, RNS and other reactive species, responsible, when in excess, for OS, can be controlled by the action of antioxidants such as α-lipoic acid (LA), however, it exerts most of its effects at high micromolar concentrations. There is an upraising interest in derivatives of LA, since molecular combinations (hybrids) obtained by coupling LA with a bioactive amino-substituted moiety may exhibit multifunctional activity. This work is organized in two inter-related parts. At first, pharmacologically active pterocarpanquinones were studied electrochemically, in aprotic and protic media, using glassy carbon working electrode. The compounds showed complex redox behavior, with evidence of additional waves related to structural changes. The products of the electroreduction of pterocarpanquinones have been shown to react with oxygen, indicative of ROS generation and explaining, in part, the reported cytotoxic effect. Additionally, the interaction with DNA of the most promising derivative, LQB-118, was investigated and showed to be negative. The second part of this study aimed to obtain amides from the reaction of LA with aromatic amines, to be evaluated toward their antioxidant protective effects against lipid peroxidation, along with their electrochemical profile. Three derivatives were obtained, being the methylthio derivative, LA-SCH3, reported for the first time in the literature. In search for the best correlation between the antioxidant properties of derived amides and their lipophilicity, we have calculated the coefficient of partition n-octanol-water (log P). The protection against lipid peroxidation was evaluated using a model of peroxyl radical-mediated lipid peroxidation using a modified membrane (unilamellar soybean lecithin). Lipid peroxidation assays showed that all compounds protected the membrane, and the LA-OH had similar protective effects on membrane as Trolox and more effective than its precursor, LA. The protective effect shown here is relevant, since the molecular hybridization performed in this study favored the protection of the membrane. IC50 value for LA-OH was obtained as well as its electrochemical profile in protic medium, with evidence of two oxidation peaks, characteristic of its multifunctional characteristics, represented by phenolic and disulfide groups.